THE EFFECT OF EXTERNAL DEBT SERVICE ON EDUCATION ACCESS IN KENYA - Pauline Chepkwisich Tarit; Wahyu Widodo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the effect of external debt service on access to primary education in Kenya using annual data from 1970 to 2023. The analysis applies the Autoregressive Distributed Lag (ARDL) model to estimate both the short-run and long-run relationships between primary school enrollment, external debt service, external debt stock, government expenditure on education, and economic growth. The findings reveal a stable long-run relationship among the variables. External debt service has a negative and statistically significant effect on primary school enrollment, suggesting that rising debt repayment obligations reduce fiscal space for education. In contrast, external debt stock shows a positive relationship with enrollment, indicating that external borrowing can support education access when allocated productively. Government expenditure on education has a positive but insignificant effect, while economic growth is negatively associated with enrollment. The results suggest that sustainable debt management and more efficient public spending are essential for protecting education access and long-term human capital development in Kenya.